Atypical Sjögrenʼs Syndrome Initially Presenting as Lymphocytic Interstitial Pneumonitis followed by Immune Thrombocytopenia - Mehmood, Maham; Jog, Abhishrut; Niazi, Masooma; Tieng, Arlene; Franchin, Giovanni (Case Reports in Rheumatology, 2021)
Background. Sjögrenʼs syndrome is an autoimmune disease characterized primarily by decreased exocrine gland function leading to eye and mouth dryness. Extraglandular manifestations occur less frequently. Case Report. A 74-year-old man with hypertension was admitted with productive cough and fever. On physical examination, he had bilateral lower lung decreased breath sounds. A chest radiograph showed bibasilar patchy infiltrate. Laboratory studies revealed hemoglobin of 11.9 g/dL, white blood cell count of 16,000/uL, and platelet count of 250,000/uL. Empiric antibiotic therapy was begun for suspected community acquired pneumonia, and then he was discharged home. However, his cough recurred. Chest computed tomography demonstrated adenopathy throughout the mediastinum and multiple ill-defined patchy groundglass opacities with a lower lobe prominence. He underwent a transbronchial biopsy to rule out malignancy; however, it showed lymphocytic interstitial pneumonitis. Antinuclear antibody was 1 : 80 homogeneous, and anti-SSA antibody was 6.3 AI (normal <1.0 AI). The patient was treated with prednisone 20 mg/day with marked improvement in his symptoms. Repeat chest computed tomography showed decreased groundglass opacities and decreased mediastinal lymph nodes. After more than a year, he was readmitted due to petechiae on his buccal mucosa and a platelet count of 2000/μL. The patient was started on prednisone 80 mg/d and intravenous immunoglobulin 80 g/d for 2 consecutive days. The platelet count eventually increased to 244,000/μL. Conclusion. We report a rare presentation of Sjogrenʼs syndrome manifesting as acute lymphocytic interstitial pneumonitis and followed by immune thrombocytopenia. Both extraglandular manifestations responded well to corticosteroid therapy.